The M|D|? queue busy period distribution - Ferreira, M. A. M. (Journal of Mathematics and Technology, 2014)
The M|D|? queue system busy period distribution is intensively studied because, due to its probability density function quite easy interpretation, it may serve as a clue to interpret M|G|? systems, with other service time’s distributions, busy period distributions. In this work the M|D|? queue system busy period distribution parameters are exactly computed and its probability density function is interpreted and explained. The only problem is how to compute the distribution function, for which an algorithm is presented and exemplified its application.